Comparison of identifications of human and animal source gram-negative bacteria by API 20E and crystal E/NF systems. - Peele, D (1997)
This study compared the abilities of API 20E and BBL Crystal E/NF identification systems to correctly identify human and animal source gram-negative bacilli of known identifications, as provided by the American Type Culture Collection, Rockville, Md., and the Research Diagnostic and Investigative Laboratory, Columbia, Mo. Also addressed in the comparison are the cost, the relative ease of performing and interpreting the tests, and the potential problems surrounding each system. The two systems were comparable in terms of their respective costs and abilities to identify the bacteria tested. The cost per test was calculated as $4.69 for API 20E and $4.62 for Crystal E/NF. Of the animal source bacteria tested, Crystal E/NF identified 68% to the correct genus and species and 90% to the correct genus or group. The remaining 10% of the animal source bacteria were unidentified by Crystal. Human source bacteria tested by BBL Crystal E/NF gave very similar results: 47% correctly identified to genus and species, 90% correctly identified to genus or group, 7% unidentified, and 3% incorrectly identified. API 20E results were as follows for animal source bacteria: 53% correctly identified to genus and species, 76% correctly identified to genus or group, and 24% unidentified; the results for human source bacteria were as follows: 40% correctly identified to genus and species, 83% correctly identified to genus or group, and 17% unidentified. API 20E has a slightly more labor-intensive protocol for setting up the test than BBL Crystal E/NF but produced fewer questionable results.